Stress variations near surfaces in diamond-like amorphous carbon - Fyta, Maria G.; Kelires, Pantelis C. (My University, 2000)
Using Monte Carlo (MC) simulations within the empirical potential approach, we examine the effect produced by the surface environment on the atomic level stresses in tetrahedral amorphous carbon. Both the distribution of stresses and the distributions of sp2 and sp3 atoms as a function of depth from the surface are highly inhomogeneous. They show the same close relationship between local stress and bonding hybridization found previously in the bulk of the material. Compressive local stress favors the formation of sp3 sites, while tensile stress favors the formation of sp2 sites.
Keywords: Carbon; Hybridization